Business model canvas : ST Clothing / Nur Izzati Ismail - Ismail, Nur Izzati (2020)
ST Clothing is one of the biggest clothing brands in Malaysia which offers a line of clothing that is fashionable and trendy. The product that our company wish to renovate is raincoat. The problem that arises about this product is the raincoats are not able to provide warm to the people who wears it even though it kept them dry. So, problem arises when majority of the customer that they cannot used the raincoat to keep them warm which make them protect from rain but still exposed to cold. Other than that, the original product used the material that was not eco- friendly like plastic and PVC that may bring danger to the ecosystem as the product is the one time used. The only way to make it happen in manageable manner is by doing BMC. By conducting business model canvas before anything, my company get to see the clear picture of how the new renovation will take place in customer’s eye, how its potential to be in the market, and what is so powerful about this product compared to the competitors. The objectives of this renovation are that I want to make it as the flexible clothes that is suitable to wear either it is raining, snowing or in cold weather. . Basically, I want to add water resistance fur that able to keep the people who wears it feel warm. The fur that keep the wearer warm must be skin- friendly and eco- friendly. The raincoats that was sold in the markets have the functions of durable and waterproof, light-weight and easy to pack, and breathable but it did not provide warm. Last but not least, I wish to make advancement on the raincoat by creating it using only eco- friendly materials, even though the product still contained the material of plastic but it durable enough to be used in a very long time before dispose. That way, we can avoid environment pollution.